Manajemen Terapi Acute Kidney Injury (AKI) - Suherman, Auriva Renasha; Kurniati, Intanri; Hadibrata, Exsa (Medula, 2024)
Acute Kidney Injury (AKI) is a syndrome characterized by decreased urine production and increased serum creatinine. AKI is a complication in 10 to 15% of patients in hospital and the incidence of AKI in the Intensive Care Unit (ICU) is 20 to 50%. AKI has 3 stages and based on etiology it is divided into 3, namely pre-renal, renal, and post-renal. AKI can be a complication of disease and can cause complications up to end-stage kidney disease. Biomarkers of AKI are not only a guide in diagnosis, but also a guide in the management of AKI. Prevention and management of AKI needs to be carried out in patients. Several AKI treatments that can be carried out include the administration of isotonic crystalloid, Hydroxerthylstarch, vasopressors, diuretics, vasodilators, GF intervention, glycemic control, and nutritional support.